2019
DOI: 10.1038/s41385-019-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intestinal microbiota by glycyrrhizic acid prevents high-fat diet-enhanced pre-metastatic niche formation and metastasis

Abstract: High-fat diet (HFD) promotes lung pre-metastatic niche formation and metastasis. Thus, there is an urgent need to identify the underlying mechanisms and develop strategies to overcome them. Here we demonstrate that glycyrrhizic acid (GA) prevents HFDenhanced pre-metastatic niche formation and metastasis through gut microbiota. GA reduced HFD-enhanced myeloid-derived suppressor cell recruitment, pro-metastatic protein S100A8/A9 expression and metastasis burden of 4T1 breast cancer and B16F10 melanoma, accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 48 publications
2
38
0
1
Order By: Relevance
“…Several studies have described the ability of immunomodulatory drugs to modulate the gut microbiota, inducing dysbiosis [44] or improving the dysbiotic condition found in several pathologies [45]. Last year, the way in which gut dysbiosis is displayed in DOCA-salt hypertension was reported [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the ability of immunomodulatory drugs to modulate the gut microbiota, inducing dysbiosis [44] or improving the dysbiotic condition found in several pathologies [45]. Last year, the way in which gut dysbiosis is displayed in DOCA-salt hypertension was reported [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Xie et al reported in mice that the increase of Desulfovibrio in feces was positively correlated with the increase of LPS levels in feces, liver, and blood [45]. Qui et al reported that ingestion of a high-fat diet in mice increased fecal Clostridium and Desulfovibrio , and oral administration of these bacteria to the normal chow-fed mice increased fecal and blood LPS levels [158]. These reports suggest that Desulfovibrio plays an important role as a source of LPS in the intestine.…”
Section: Association Of Dietary Factor-induced Reduction Of Blood mentioning
confidence: 99%
“…High-fibre diets induce the production of short-chain fatty acids by gut bacteria, which are transported systemically to the lung, where they exert anti-inflammatory actions and ameliorate AAD in mice [47]. In contrast, a lipid-rich diet alters the microbiota and promotes metabolic inflammation [50], and has been associated with premetastatic niche development in lung cancer [51]. However, the detailed mechanisms of action remain unclear.…”
Section: Role Of the Environment In Shaping The Lung Microbiomementioning
confidence: 99%